PERBANDINGAN LABA PAGANG GADAI SAWAH DENGAN RATA-RATA LABA DEPOSITO PERBANKAN SYARI’AH (Studi Kasus Nagari Padang Tarok Kecamatan Baso) - Ahmad Omar Fayyadh (UIN Mahmud Yunus Batusangkar, 2022)
This research is needed because there is an assumption in the community that the profit in the pawn handle of rice fields is exploitative and blackmails people who are in trouble and need. This research was conducted in Nagari Padang Tarok, Baso District, Agam Regency, West Sumatra and was conducted based on an Islamic economic perspective. The method used in this study is a descriptive qualitative method, which is to describe the problems discussed clearly and analyze them in depth and in an orderly manner. The results of this research analysis are then presented in the form of a comparison which produces a conclusion from the data obtained. The data obtained in this study were obtained through interviews conducted with several communities in Nagari Padang Tarok. The data obtained are then analyzed using descriptive qualitative methods. The results of the research findings in this study are that the rice field pawn handles carried out by the community in Nagari Padang Tarok are not exploitative. This finding was obtained after comparing the average percentage of rice field pawn trading profit with the average percentage of shari'a banking deposit profit in Indonesia. The data analyzed show that the rice field pawn handles carried out by the people of Nagari Padang Tarok are not exploitative, even it helps the economy of the Nagari Padang Tarok community in meeting their living needs.